Assessing Pilgrims’ Satisfaction Toward the 2025 Regular Hajj Services in Bojonegoro - Nanang Setiawan; Imroatul Azizah; Ahmad Manshur; Amanulloh Amanulloh; Abdulloh Hafidz; Nufudz Aqthor (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study aims to assess the level of pilgrim satisfaction with the Regular Hajj services in 2025 in Bojonegoro Regency. A survey method was employed, involving 235 regular Hajj pilgrims in 2025 as respondents. The findings indicate that the overall satisfaction level falls into the high category, with a percentage of 79.7% and an average score of 3.98 on a 5-point scale. The assessment covered ten service aspects: travel document processing, religious guidance, embarkation/debarkation, air transportation, ground transportation, accommodation, meals, Armuzna services, Hajj information systems, and leadership of the service officers. The highest satisfaction levels were found in the aspects of air transportation, embarkation/debarkation, and religious guidance. Conversely, the lowest satisfaction levels were recorded in the areas of Armuzna services, ground transportation, and meals. Theoretically, this study contributes to the literature on Hajj pilgrim satisfaction through a multidimensional service approach. Practically, these findings may serve as input for Hajj organizers in their efforts to improve service quality, particularly in aspects with low levels of satisfaction